ANALISIS FAKTOR INTERNAL DAN EKSTERNAL KESULITAN MEMBACA SISWA DI SD YPK SILO KABILOL, RAJA AMPAT - Elda Gasilce Aitem; Desti Rahayu; Kartika Tiara (Adisam Publisher, 2025)
This study aims to analyse the internal and external factors that cause reading difficulties among Year 2 students at YPK Silo Kabilol Primary School, Tiplol Mayalibit District, Raja Ampat Regency, Southwest Papua. The background to this study is the low level of early reading skills in lower primary grades, which has an impact on the overall learning process of students. The study used a qualitative descriptive approach with four second-grade students and one homeroom teacher as subjects. Data collection techniques included observation, interviews, and documentation. The results of the study show that students' reading difficulties are caused by two main categories: (1) internal factors, including age, readiness to learn, delayed cognitive development, concentration disorders, and low motivation to read; and (2) external factors, including lack of family support, limited school facilities, conventional learning methods, and the geographical conditions of remote areas. Teachers overcome reading difficulties through the application of phonetic methods, the use of visual-audio media, individual approaches, cooperation with parents, and daily reading habits. These findings emphasise the importance of collaborative and contextual approaches in improving basic literacy in 3T areas.